2016
DOI: 10.5897/ajb2016.15444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Anopheles gambiae sensu stricto Giles (formerly Anopheles gambiae Savannah Form) in Kamuli District, Uganda

Abstract: Anopheles gambiae sensu stricto Giles (formerly A. gambiae S molecular form), the largely anthropophilic species, is reportedly the most important malaria vector in Uganda among the A. gambiae complex species. Indoor and outdoor human-biting mosquitoes were caught for four consecutive nights in each of 48 households in Kamuli district using human-baited bed net traps for subsequent identification of the principal Anopheles sibling species responsible for transmitting malaria. Sibling species under the A. gambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…revealed that the predominant sibling malaria vector species in the study area is A. arabiensis (95.5%). Studies in other parts of the country, for example, Tororo [ 16 ], Kamuli [ 39 ], Jinja [ 18 ], have documented sympatric existence of A. arabiensis with A. gambiae s.s. and A. funestus [ 20 ]. These three species have also been reported as the main vectors of Plasmodium falciparum malaria in Sub-Saharan Africa [ 8 , 25 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…revealed that the predominant sibling malaria vector species in the study area is A. arabiensis (95.5%). Studies in other parts of the country, for example, Tororo [ 16 ], Kamuli [ 39 ], Jinja [ 18 ], have documented sympatric existence of A. arabiensis with A. gambiae s.s. and A. funestus [ 20 ]. These three species have also been reported as the main vectors of Plasmodium falciparum malaria in Sub-Saharan Africa [ 8 , 25 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerged adults from the reared larvae were morphologically identified using simplified standard morphological keys adopted from Gillies & Coetzee (1987) to deduce the species present (Kabbale et al, 2016). Whilst to check and to improve on the precision of the morphological identification, emerged adult mosquitoes were observed under a dissecting microscope and identified using standardized morphological keys as by Coetzee (2020).…”
Section: Malaria Vectors Diversity and Abundance Detectionmentioning
confidence: 99%
“…However, this could not rule out the fact that there could be other prevailing ecological or human factors in Busia district responsible for their proliferation such as increased permanent breeding sites. The A. funestus that dominated in Busia district is known to breed all year round and prefer permanent, stagnant water bodies, while Anopheles gambiae sensu lato breed in temporary human created water bodies including rice paddies, pools, puddles, construction sites and hoof prints which were more prevalent in Tororo than Busia district [2,5,28].…”
Section: Malaria Vectors Diversity and Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…The multiplex PCR technique was used for molecular characterization of members of the An. gambiae complex as described by Okwa et al (2007), Brogdon and Chan (2010) and Kabbale et al (2016). Direct method was used where legs and (or) wings of each morphologically identified member of An.…”
Section: Molecular Identification Of Anopheles Speciesmentioning
confidence: 99%